Thoracic magnetic resonance imaging in non-tuberculous mycobacterial pulmonary disease: Characteristics and potential implementation. - Ieuan Edward Shepherd Evans; Timothy Baird; Charles S Haworth; Christopher Johnson; Helen Barker; Uta Hill; Dorothy Grogono; Odiri Eneje; Nicholas Screaton; Andres Floto (PLoS ONE)
Background Non-tuberculous mycobacteria (NTM) are pulmonary pathogens with increasing incidence and prevalence worldwide, with people with cystic fibrosis (pwCF) traditionally considered at high risk of disease development. The imaging assessment of NTM-pulmonary disease (NTM-PD) relies heavily on high-resolution computed tomography (HRCT). However, due to lengthy treatment regimens and the need for long-term follow-up, serial HRCT's result in progressive exposure to ionizing radiation; a particular concern in younger people. Methods We performed a retrospective cohort study of patients who had undergone serial thoracic magnetic resonance imaging (tMRI) scans to monitor NTM-PD as a novel tool to image the lung with a view to creating an algorithm for the utility of tMRI in the management of NTM-PD. Results Thirty-six patients, of which twenty-four had a diagnosis of CF, with suspected or confirmed NTM-PD underwent serial tMRI between 1st January 2013 and 30th June 2018. A total of 117 serial tMRI's were performed (mean number per patient 3.25; range 2-6). The associated clinical impact that each serial MRI had on management, deemed as the utility of tMRI, found that all tMRI's were classified as aiding management with 60 (51.3%) altering management. tMRI's were more likely to alter management in the non-CF cohort than the CF cohort (69.4% vs. 43.2%). No imaging-related adverse events were reported across the 117 tMRI's. Conclusion This study highlights that tMRI may hold promise as a monitoring tool in NTM-PD and should be prospectively evaluated in the monitoring of individuals with NTM-PD.